2007
DOI: 10.1007/s00003-007-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins and dioxin-like PCBs in fish and fishery products on the German market

Abstract: Concentrations of polychlorinated dibenzodioxins, dibenzofurans and dioxin-like PCBs in the edible part of fish and in fishery products were studied to gain an overview on actual contaminant levels on the German market.The investigation focused mainly on fish species with higher fat content and was orientated to cover all important fishing grounds for the supply of the German market. Pooled samples of 32 different fish species, 5 crustacean and mussel species and some typical products were analysed. Fish with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
4
0
3
Order By: Relevance
“…In terms of indicator PCBs, the levels found in this study are much lower than the levels found by Bayarri et al (2001). Dioxin and dl-PCBs (TEQ) contamination levels of whiting found in this study are higher, while the levels of anchovy are similar compared to the results found by Karl and Ruoff (2008). It is seen that the dioxin and PCB levels found in this study are higher than the results found in Greece by Papadopoulos et al (2004) and dioxin levels are similar to the results found in Italy by Taioli et al (2005).…”
Section: Resultssupporting
confidence: 56%
“…In terms of indicator PCBs, the levels found in this study are much lower than the levels found by Bayarri et al (2001). Dioxin and dl-PCBs (TEQ) contamination levels of whiting found in this study are higher, while the levels of anchovy are similar compared to the results found by Karl and Ruoff (2008). It is seen that the dioxin and PCB levels found in this study are higher than the results found in Greece by Papadopoulos et al (2004) and dioxin levels are similar to the results found in Italy by Taioli et al (2005).…”
Section: Resultssupporting
confidence: 56%
“…Außer Acht gelassen werden sollte in diesem Zusammenhang auch nicht, welchen gelegentlichen ImageVerlust das Nahrungsmittel Fischerzeugnisse immer wieder bei den Verbrauchern hinnehmen muss, wenn über die Anreicherung diverser, nicht gerade gesundheitsfördernder Substanzen, wie z. B. Schwermetalle und Dioxine, in Fischen berichtet wird (Roberts, 2006;Ende, 2008;Karl und Ruoff, 2008;Stiehl et al, 2008aStiehl et al, und 2008b.…”
Section: Ein (Potentielles) Zukünftiges Versorgungsdilemma Und Ein Weunclassified
“…B. Karl und Ruoff, 2008;Ende, 2008;Stiehl et al, 2008aStiehl et al, und 2008b ab mit Meldungen über die ernährungsphysiolo-gischen Vorteile, die der Verzehr von Fischen mit sich bringt. Im Hinblick auf diese zwiespältige Lage erscheint es angebracht, hier zumindest summarisch aufzuzeigen, was der Verbraucher -ungeachtet der möglichen Schadstoffbelastung -nach dem derzeitigen Erkenntnisstand für gesundheitliche Vorteile durch den Verzehr von Fisch, insbesondere durch die darin enthaltenen langkettigen Omega-3-Fettsäuren, erwarten kann.…”
Section: Introductionunclassified
“…Furthermore, based on these data, we intented to determine the daily intake of dioxins and PCBs from food of animal origin. Further data on fish and fishery products as well as on feed have been published recently (Karl and Ruoff 2008;Schwind et al 2010).…”
Section: Introductionmentioning
confidence: 99%